2015
DOI: 10.1002/sec.1272
|View full text |Cite
|
Sign up to set email alerts
|

First step towards preserving the privacy of cloud‐based IDS security policies

Abstract: Traditional intrusion detection systems, managed by organizations themselves, have already evolved towards cloud architectures. While benefitting from all the advantages of the cloud computing paradigm, they are also suffering from one of its main drawbacks-privacy issues. As intrusion detection system security policies expose critical information regarding the organization such as vulnerabilities, sharing this information with cloud service providers raises serious privacy concerns. The following paper propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In turn, the results achieved in Solution III in the private cloud are comparable to those achieved in the UNIPRIV. This means that the engine used by the UNIRPRIV in the private cloud achieves comparable performance results to the most performant engine presented by the authors …”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…In turn, the results achieved in Solution III in the private cloud are comparable to those achieved in the UNIPRIV. This means that the engine used by the UNIRPRIV in the private cloud achieves comparable performance results to the most performant engine presented by the authors …”
Section: Resultsmentioning
confidence: 69%
“…It is shown that the implementation of the DTE in software is fully justified. Finally, performance results of the UNIPRIV are compared with performance results of dedicated privacy‐preserving solutions for IDS service that were presented by the authors …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to such technologies as AT&T NBFWS or Virtela ESC, these can be outsourced to the cloud, resulting in significantly reduced management overhead, decreased Total Cost of Ownership (TCO), improved business agility, and so on [5]. However, because of a lack of mechanisms preventing the CSP from having an insight into the customer' firewall policy, there are still issues of information confidentiality and privacy [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%